1999
DOI: 10.1007/s003810050442
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided puncture of a Dandy-Walker cyst via the lateral and III ventricles

Abstract: Since the Dandy-Walker syndrome was first described by Dandy and Blackfan, Taggart and Walker, the many variants of posterior fossa anomalies, the appropriate management of these malformations and the clinical outcome have been the subjects of controversy. Surgery of the posterior fossa with membrane excision was initially the preferred method of treatment. Unfortunately, there was a high rate of complications, and many of the patients treated in this way still needed a shunting system. Ventricular-peritoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…To avoid catheter migration out of the cyst with the growing size of the head, which would make possibly more difficult shunt revision necessary, the surgeon selected a catheter which was longer than needed for the mere connection of the ventricle and cyst. Cedzich et al [30] had the same idea of connecting the posterior fossa cyst with the supratentorial ventricular system to allow monocompartmental shunt placement. In contrast to our technique, they perforated the dorsal third ventricular wall to gain access to the posterior fossa cyst.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid catheter migration out of the cyst with the growing size of the head, which would make possibly more difficult shunt revision necessary, the surgeon selected a catheter which was longer than needed for the mere connection of the ventricle and cyst. Cedzich et al [30] had the same idea of connecting the posterior fossa cyst with the supratentorial ventricular system to allow monocompartmental shunt placement. In contrast to our technique, they perforated the dorsal third ventricular wall to gain access to the posterior fossa cyst.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our technique, they perforated the dorsal third ventricular wall to gain access to the posterior fossa cyst. In our patient, there was no straight trajectory through the foramen of Monro into the posterior fossa cyst, which excluded the use of this surgical technique [30]. Furthermore, dorsal third ventricular wall perforation was considered to be more risky than the occipitobasal transtentorial approach.…”
Section: Discussionmentioning
confidence: 99%
“…While open cyst fenestration has gained recent proponents [12], ventriculoperitoneal (VPS) and/or cystoperitoneal shunting (CPS) remain the mainstays of treatment [3,4,5,6,7,8,9,10,11]. According to the literature, combined VPS and CPS is needed for satisfactory decompression of the Dandy-Walker cyst and hydrocephalus in 16 and 92% of all cases [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Cedzich et al [13] described the drainage of both the supratentorial ventricles and posterior fossa cyst via a single ventricular catheter placed under ultrasound guidance via a frontal burr hole. The authors reported excellent drainage of both compartments with this single shunting system, thereby minimizing the potential malfunction risk while maintaining transtentorial pressure equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…A multiperforated single catheter was placed under ultrasonic guidance via a frontal burr hole into both compartments through the dorsal third ventricular wall. 6) Good results were obtained with readily available equipment, but the inability to visualize the intraventricular systems carries the risk of injury to intraventricular vessels. Nonetheless, placement of the modified single catheter was reportedly safe and effective.…”
Section: Discussionmentioning
confidence: 91%